Genetic Base of Wheat Cultivars Recommended in Nepal (Nepal Agriculture Research Journal, 2010)
Plant breeding success is dependent, in part, upon the genetic diversity found within geneticresources. The genetic base of wheat (Triticum aestivum L.) cultivars recommended in Nepal is notwell characterized. Therefore this study was carried out to quantify the genetic base of Nepalesewheat cultivars by coefficient of parentage (COP). Analysis of pedigree information was based onInternational Wheat Information System of the International Center for Maize and WheatImprovement (CIMMYT), which consists of WCOP for calculation of COP and WPDEND forgenerating Mendelgram with contribution of ancestors to the cultivar if fully expanded. Onehundred eighteen ancestors from 23 countries were identified in the pedigree of 24 recommendedNepalese cultivars. Of these, 32 ancestors contributed at least 1% each to the genetic base ofNepalese cultivars, with a total contribution of 79%. Ancestors originating from USA contributed19.8% of the genes, India 11.2%, Japan 9.5%, Argentina 7.5%, Kenya 7.5% Australia 6.2%, Brazil5.6%, Canada 5.5%, Italy 4.1% and remaining from other countries. At 30% similarity, 18 clusterswere formed with largest cluster of five members. None of Nepalese landraces were traced in thepedigree of these cultivars. Relatively large amount of diversity in Nepalese cultivars exits based ontheir genetic background although small number of cultivars is recommended for cultivation.Key words: Coefficient of parentage; diversity; Triticum aestivum; wheat breedingDOI: 10.3126/narj.v6i0.3338Nepal Agriculture Research Journal Vol.6 2005 pp.1-9